2015
DOI: 10.1002/acp.3160
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Event Centrality in Memory Models of PTSD

Abstract: The consequences of events for well-being are influenced by individual and situational factors that are often studied in isolation. In the research reported here a large (N = 489) nonclinical sample of college students reported their most traumatic event, PTSD symptoms, depressive symptoms, personality traits, and characteristics of their event memory. This study achieved three major goals. First, we identified the highest types of stress event types in this population as disruptions of interpersonal relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 73 publications
2
28
0
8
Order By: Relevance
“…Notably, the CGAS model went further to observe the ability of centrality to mediate between types of rumination, and between intrusive rumination and PTS. This finding is supported in recent literature that views centrality as a facilitator of other cognitive processes after adversity, in part due to the increased accessibility of salient memories (Fitzgerald et al ., ; Lancaster et al ., ). Centralized events create internal, stable, and global attributions, leading the survivor to believe their adversity is related to personal characteristics (Berntsen & Rubin, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, the CGAS model went further to observe the ability of centrality to mediate between types of rumination, and between intrusive rumination and PTS. This finding is supported in recent literature that views centrality as a facilitator of other cognitive processes after adversity, in part due to the increased accessibility of salient memories (Fitzgerald et al ., ; Lancaster et al ., ). Centralized events create internal, stable, and global attributions, leading the survivor to believe their adversity is related to personal characteristics (Berntsen & Rubin, ).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, few studies explore how event centrality relates to other post‐event cognitions associated with PTG or PTS. For example, centrality can mediate between cognitive responses across a range of event types (Fitzgerald, Berntsen, & Broadbridge, ), by making memories of adverse events more accessible, which then prompt other cognitive processes conducive of growth, such as life‐narrative organization (Boals, ). Growth then occurs when the event is assimilated into the survivor's perspective of themselves and the world (Lancaster et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also have found positive correlations between the CES and the personality trait Openness (e.g., Berntsen, Rubin, & Siegler, 2011; Ogle, Rubin, & Siegler, 2014), consistent with a general tendency for characteristics of autobiographical memory to be correlated with Openness (e.g., Rasmussen & Berntsen, 2010; Rubin & Siegler, 2004). Findings are mixed regarding the relation between the CES and the personality traits of Agreeableness, Conscientiousness, and Extraversion (e.g., Fitzgerald et al, 2016; Ogle et al, 2014). …”
Section: The Theoretical Background For the Ces And Empirical Findingsmentioning
confidence: 99%
“…Across populations, event centrality has remained a unique predictor of variance in PTSS after controlling for anxiety, depressed mood, dissociation, as well as other known predictors 13,14,20,21 . In addition to cross-sectional evidence, event centrality has been shown to predict PTSS in longitudinal and prospective studies following stressful/traumatic life events [22][23][24] .…”
mentioning
confidence: 99%
“…In the psychological trauma literature, event centrality has proven to be a consistently strong predictor of PTSS [13][14]21 . In the current study, we found event centrality is not only common amongst spinal cord injury patients, it also predicts unique variance in two important psychological outcomes -PTSS and perceived disability.…”
mentioning
confidence: 99%